Pengembangan Metode Improve Musik Mendukung Peningkatan Kemampuan Kreatif dan Kecerdasan Musik - Prita Khairunnisa; Nuril Huda; Haerussaleh (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The art of music is part of student sub-subjects at primary and secondary education levels, and is an extra school curriculum activity with the hope of increasing interest that supports multiple intelligences (music) and student creativity. The music practice process has several learning method approaches, one of which is the improve method which is seen as able to support increasing students' intelligence and creativity. So the aim of this research is to test the effect of music improvement training methods on students' creativity and intelligence. Real experimental research was carried out using a pretest-post test design model involving a control group. Data was collected through checklists (assessment sheets) from three music instructors to measure musical creativity and intelligence. The results of the hypothesis testing analysis through the paired sample t test showed that there was a positive and significant influence of the improvement method on musical intelligence, both in the experimental group and the control group; there was a positive and significant influence of the music improvement method on students' creativity in the experimental group, whereas in the control group there was no evidence of an increase in creativity; and there is a significant difference in musical intelligence and increased creativity between the experimental group, namely students who practice music using improved methods, and the control group, namely students who practice using non-improved methods.